Redeeming grace : Ruth's story - Smith, Jill Eileen, 1958- (Smith, Jill Eileen, 1958- Daughters of the promised land, 2017)
When famine visits Bethlehem, Boaz holds out hope for rain while his relative Elimelech moves his wife Naomi and their sons to Moab. For a while, it appears the Lord is blessing Elimelech's family, and his sons marry two lovely Moabite women. But calamities strike, one after another, leaving Naomi alone in a foreign land with only her childless daughters-in-law for comfort. When news reaches Naomi that the famine in Bethlehem has lifted, only Ruth will hazard the journey to her mother-in-law's homeland. Destitute and downhearted, Naomi resigns herself to a life of bitter poverty, but Ruth holds out hope for a better future. And Boaz may be the one God has chosen to provide it.